ANALYSIS OF STUDENTS' COLLABORATION SKILLS IN PANCASILA EDUCATION LEARNING IN ELEMENTARY SCHOOLS - Yulia Eka Rahmayanti; Reza Rachmadtullah (Media Inovasi Pendidikan dan Publikasi, 2024)
Students' collaboration skills in Civics Education at Elementary School is an intriguing and relevant topic for research because it involves not only explaining citizenship education but also developing crucial social and collaborative skills necessary in an increasingly complex society. Collaborative projects, where students work together to complete challenging tasks, stimulate discussions, and encourage joint problem-solving, play a key role. Through these projects, students not only learn about the importance of teamwork but also understand that their responsibilities as members of society are intertwined with cooperation and positive contribution. This study aimed to investigate the efforts of teachers in fostering students' collaboration skills in Civics Education and assess the extent of improvement in students' collaborative skills as a result of citizenship education, particularly concerning responsibility.